Fig. S4 and Tables S1–S3: Effects of melt-percolation, refertilization and deformation on upper mantle seismic anisotropy: constraints from peridotite xenoliths, Marie Byrd Land, West Antarctica - V. Chatzaras; S.C. Kruckenberg (2021)
Calculated seismic properties of individual xenoliths from Marie Byrd Land, West Antarctica (S4), geographical coordinates of the volcanic centres (Table S1), mineral major element composition (Table S2) and synthetic seismic properties by modal composition (Table S3)